2016
DOI: 10.1039/c6md00208k
|View full text |Cite
|
Sign up to set email alerts
|

Radiolabeled analogs of neurotensin (8–13) containing multiple 1,2,3-triazoles as stable amide bond mimics in the backbone

Abstract: Radiometallated regulatory peptides are a promising class of radiopharmaceuticals for the diagnosis (imaging) and therapy of cancer in nuclear oncology. A limitation of such peptides employed as tumor-specific vectors is represented by their low stability in vivo. Stabilization of the peptides against proteolytic degradation by, e.g., structural modifications, can improve their tumor-targeting properties. We here report an application of our recently introduced peptide stabilization methodology, which involves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…35 However, to further expand the applications of poly-1,2,3-triazoles in the areas of drug synthesis, ion recognition, chemicobiology, supramolecular chemistry and others, much work still remains. 11,36 The mini review presented here can hopefully serve as a guide to better design and fabrication of functional poly-1,2,3-triazoles for addressing the problems existing in scientic communities and real-world industries. Although a signicant advance has been achieved for synthesis and potential applications of poly-1,2,3-triazole-based functional materials in the past few decades, there still exist a number of challenges.…”
Section: Discussionmentioning
confidence: 99%
“…35 However, to further expand the applications of poly-1,2,3-triazoles in the areas of drug synthesis, ion recognition, chemicobiology, supramolecular chemistry and others, much work still remains. 11,36 The mini review presented here can hopefully serve as a guide to better design and fabrication of functional poly-1,2,3-triazoles for addressing the problems existing in scientic communities and real-world industries. Although a signicant advance has been achieved for synthesis and potential applications of poly-1,2,3-triazole-based functional materials in the past few decades, there still exist a number of challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent investigations focused on the incorporation of multiple triazoles in the backbone of NT(8–13) [ 98 ]. Building on the results of the triazole scan discussed above, the triazolo-peptidomimetics NT11 and NT12 with a simultaneous substitution at PEG 4 -Arg 8 and Arg 8 -Arg 9 for the Ile 12 and Tle 12 analogue were synthesised and tested in vitro.…”
Section: Applicationsmentioning
confidence: 99%
“…47 In contrast to [ 177 Lu]Lu-NT 1c, which bears an additional triazole moiety at the N-terminus compared with [ 177 Lu] Lu-NT-VI (entry 5, Table 3) and has sustained affinity for NTS1, the introduction of a second triazole moiety into the backbone of NT IX led to a substantial decrease in receptor affinity, suggesting that employing multiple amide-to-triazole substitutions in molecules with biological function will require case-by-case studies regarding the preservation of receptor affinity. 48 To date, only a few studies have reported on the preclinical radiotherapeutic efficacy of 177 Lu-labeled NT peptide analogs. The first preclinical study on a 177 Lu- Table 3).…”
Section: Peptides Radiolabeled With Lu-177 For Endoradiotherapymentioning
confidence: 99%
“…They systematically studied the influence of the triazole moiety in different positions of the amino acid sequence of the peptide, revealing that [ 177 Lu]Lu‐NT‐VI (entry 4, Table ) with a K d of 8.8 nM and its stabilized Tle 12 ‐for‐Ile 12 substituted analog ([ 177 Lu]Lu‐NT IX, entry 4, Table ) with a K d of 214 nM and a 98% 4‐hour stability in serum in vitro were interesting tracers for further developments of NT‐based radiotherapeutics . In contrast to [ 177 Lu]Lu‐NT 1c, which bears an additional triazole moiety at the N‐terminus compared with [ 177 Lu]Lu‐NT‐VI (entry 5, Table ) and has sustained affinity for NTS1, the introduction of a second triazole moiety into the backbone of NT IX led to a substantial decrease in receptor affinity, suggesting that employing multiple amide‐to‐triazole substitutions in molecules with biological function will require case‐by‐case studies regarding the preservation of receptor affinity …”
Section: Introductionmentioning
confidence: 99%